Characterisation of Staphylococcus aureus isolates from bovine mastitis in Ningxia, Western China. (June 2021) - Chen, Cheng; Sun, Chengtao; Li, Jidong; Ji, Xing; Wang, Yang; Song, Cuiping; Wang, Guiqin
Highlights: Molecular typing of S. aureus isolates identified nine clonal complexes (CCs) and 16 spa types. Two novel sequence types (ST4066 and ST4053) were identified. There was a high prevalence of isolates (27.2%) belonging to novel sequence type ST4053. ST239-SCC mec III and ST59-SCC mec IV isolates have potential for cross-species transmission, being a public-health threat. Staphylococcus aureus from bovine milk shows severe multidrug resistance. ABSTRACT: Objectives: The aim of this study was to explore the antimicrobial resistance, virulence genes and molecular characteristics of Staphylococcus aureus from bovine mastitis cases. Methods: A total of 125 non-duplicate S. aureus isolates from bovine mastitis cases in Ningxia, China, were characterised by antimicrobial susceptibility and molecular testing to determine the antimicrobial resistance, virulence genes and molecular characteristics. Results: All methicillin-resistant S. aureus (MRSA) isolates were resistant to ampicillin, oxacillin, ceftiofur, erythromycin, gentamicin and clindamycin, with resistance to nine different categories of antibiotics observed amongst the MRSA isolates. Of the methicillin-susceptible S. aureus (MSSA) isolates, 62.1% were resistant to ampicillin and sulfisoxazole. Nine clonal complexes (CCs) and 16 spa types were identified by multilocus sequence typing (MLST) and spa typing. The dominant CCs were CC97 (51.2%) and CC50 (30.4%), while t224 (30.4%), t518 (20.0%) and t359 (16.8%) were the most common spa types. A relatively high proportion (27.2%) of the S. aureus isolates belonged to ST4053, a novel sequence type identified in this study. In addition, two CC30 MSSA isolates and two CC59 MRSA isolates were positive for Panton–Valentine leukocidin, while one CC239 MRSA isolate and three CC5 MSSA isolates were positive for TSST-1. All MRSA isolates carried the immune evasion cluster (IEC) genes, including scn (100%; 9/9) and sak (100%; 9/9), which were classified into type E. Conclusion: Our study indicates severe antibiotic resistance and complicated molecular characterisation of S. aureus causing bovine mastitis. Additional studies should be conducted to monitor infection and transmission of S. aureus .